Urgensi Filsafat Islam dalam Kurikulum PTAI - Sukamdani, M. (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2015)
This paper discusses the urgency of Islamic philosophy in the curriculum ofIslamic colleges in Indonesia. The critical description of this paper is the positivistparadigm. This then makes humans eliminate bases of theological philosophicalthought (especially Islam). Islamic education in Indonesia, in this case PTAI,instead of using the philosophy of Islam, chose to use western philosophy asa center of excellence. Islamic philosophy itself arises from the translationof philosophical works on a large scale during the Abbasid Caliphate. In itsdevelopment, Islamic philosophy has gone up and down. The most phenomenal intidal Islamic philosophy is the attack of al-Ghazali and Ibn Rushd counterattack.The philosophy of Islam in Indonesia is still quite young. However, the reasonsare not necessarily used as an argument that Islamic philosophy is not goodenough to be the basis of scientific colleges. Research, development, publication ofIslamic philosophy are continuously done to enrich the discourse. In the contextof higher education, there is now an offer to integrate and connect â€œcommonâ€secular philosophy (Islam) and al-Qurâ€™an traditions. Thus, the dichotomy ofwestern-Islam, secularity knowledge and neglect of religion and philosophy canbe resolved.Kata kunci: Islamic philosophy, curriculum, PTAI